PEMIKIRAN MUHAMMAD SA’ĪD RAMADĀN AL-BŪṬĪ TENTANG MAṢLAḤAH DAN BATASAN-BATASANNYA - Muhammad Solikhudin (Institut Agama Islam Negeri (IAIN) Kediri, 2019)
This paper attempts to unravel the concept study of Maṣlaḥah posed by al-Būṭī, in this case he also proposes clear boundaries about Maṣlaḥah aligned with the Syarī’ah Islāmiyyah. Maṣlaḥah was a pleasure, therefore, all things are dangerous must be avoided. Requirements proposed al-Būṭī, started the benefit included on Syāri’goal embodied in Islam universal basic principles five, not contrary with the alQur’an), not contrary with al-Sunnah, not contrary with Qiyas, until its existence not negate another benefit that important more or equivalent. All this suggests caution al-Būṭī in offering Maṣlaḥah concept that he woke up so it is not contrary with religious rules. The benefit must have two footing. First, will of God and secondly, human interests, both of these things as contrary, but when examined more deeply has the estuary, that is human happiness in this world and hereafter